2019
DOI: 10.1017/jfm.2019.291
|View full text |Cite
|
Sign up to set email alerts
|

Suspension Taylor–Couette flow: co-existence of stationary and travelling waves, and the characteristics of Taylor vortices and spirals

Abstract: Flow visualization and particle image velocimetry (PIV) measurements are used to unravel the pattern transition and velocity field in the Taylor–Couette flow (TCF) of neutrally buoyant non-Brownian spheres immersed in a Newtonian fluid. With increasing Reynolds number ($Re$) or the rotation rate of the inner cylinder, the bifurcation sequence in suspension TCF remains same as in its Newtonian counterpart (i.e. from the circular Couette flow (CCF) to stationary Taylor vortex flow (TVF) and then to travelling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
109
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(142 citation statements)
references
References 46 publications
25
109
8
Order By: Relevance
“…(2018) and Ramesh et al. (2019) were performed for a similar range of volume fractions, but for a lower range of Reynolds numbers . These two studies utilized slowly accelerating/decelerating ramp protocols, i.e.…”
Section: Experimental Set-up and Measurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) and Ramesh et al. (2019) were performed for a similar range of volume fractions, but for a lower range of Reynolds numbers . These two studies utilized slowly accelerating/decelerating ramp protocols, i.e.…”
Section: Experimental Set-up and Measurement Proceduresmentioning
confidence: 99%
“…Please note that these two experiments are done separately, like Ramesh et al. (2019). A few experiments were repeated on different days, and sufficient repeatability was observed.…”
Section: Experimental Set-up and Measurement Proceduresmentioning
confidence: 99%
“…We model these interactions as rotary diffusion (D r terms) in Eqs. (9) and (10). Theoretical and experimental studies have shown that rotary diffusion is an adequate model for hydrodynamic interactions between rods [30][31][32][33][34].…”
Section: Theorymentioning
confidence: 99%
“…We shed some light on this issue below by comparing the theoretical model [Eqs. (7)- (10)] to experimental data, for both steady shear flow and for the TCF instability.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation